2021
DOI: 10.1002/jmri.27815
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Based Investigation of Association Between Cerebrovascular Structural Alteration and White Matter Hyperintensity Induced by High Blood Pressure

Abstract: Background High blood pressure (BP) is a common risk factor for cerebral small vessel disease including white matter hyperintensity (WMH). Whether increased BP exacerbates WMH by impacting cerebral vascular morphologies remains poorly studied. Purpose To determine the relationships among high BP, cerebrovascular morphologies, and WMH in elderly individuals. Study Type Cohort. Subjects Eight hundred sixty‐three participants (54.2% female) from the Taizhou Imaging Study without clinical evidence of neurologic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Moreover, it has been suggested that elevated BP may affect CSVD by reshape the large intracranial arteries. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been suggested that elevated BP may affect CSVD by reshape the large intracranial arteries. 42 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that elevated BP may affect CSVD by reshape the large intracranial arteries. 42 Nevertheless, it is more likely that the above 2 processes interact with each other, forming a vicious circle, which promotes the growth of WMH. A similar vicious cycle related to morphological modifications between large and small arteries caused by hypertension has been reported previously.…”
Section: Cerebral Artery Dilation and Wmhmentioning
confidence: 99%
“…Cerebral vessel segmentation and feature extraction were completed on TOF MRA scans using the existing method with following steps: 17 1) vascular structures were enhanced using the Jerman Enhancement Filter; 18 2) the level-set based method was used to obtain vessel segmentation; 3) segmentation results were firstly checked by B.Y.Z and B.W. Segmentations with too few vascular branches, nonvascular tissue remnants, or incorrect vascular branch adhesions were re-segmented by adjusting the segmentation parameters.…”
Section: Mri Scanning and Processingmentioning
confidence: 99%
“…In this issue of Journal of Magnetic Resonance Imaging, Boyu Zhang and colleagues studied the connection between hypertension, cerebrovascular morphology, and WMH burden. 3 In their study, the authors used MRI data from 863 participants (465 had hypertension) from Taizhou Imaging Study and quantified the white matter lesion burden using automated lesion prediction algorithm based on T2-weighted fluid attenuated inversion recovery (FLAIR) images. Brain vascular morphology was studied using time-of-flight MR angiography (TOF MRA) for vessel density, tortuosity (describing the healthy curvature of individual blood vessels), branch numbers, and radius.…”
mentioning
confidence: 99%
“…However, majority of CSVD cases are sporadic, raising from vascular risk factors including hypertension. In this issue of Journal of Magnetic Resonance Imaging , Boyu Zhang and colleagues studied the connection between hypertension, cerebrovascular morphology, and WMH burden 3 …”
mentioning
confidence: 99%